2006
DOI: 10.1136/oem.2005.021139
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos exposure and biological monitoring among manufacturing workers: Table 1

Abstract: Aim: To use biological monitoring data to evaluate the soundness of job based exposure classifications. Methods: The authors studied 52 chlorpyrifos manufacturing workers and 60 referent workers to compare chlorpyrifos exposure estimations from job titles and work areas to urinary excretion of 3,5,6 trichloro-2-pyridinol (TCP), a metabolite of chlorpyrifos. Work history records and industrial hygiene monitoring data were used to establish cumulative interim exposure. Chlorpyrifos exposure during the study year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Our regression analyses showed that BuChE activity, as a biological measure of chlorpyrifos exposure, was significantly related to average TCP/Cr excretion averaged over the year of observation (a quantitative biological measure chlorpyrifos dose), a finding consistent with our previous report (Burns et al, 2006). We recognize that the relationship between measures of BuChE activity and TCP/Cr excretion is dynamic and that averaging the values for each measure throughout the year could possibly obscure or blunt the relationship between the two measures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our regression analyses showed that BuChE activity, as a biological measure of chlorpyrifos exposure, was significantly related to average TCP/Cr excretion averaged over the year of observation (a quantitative biological measure chlorpyrifos dose), a finding consistent with our previous report (Burns et al, 2006). We recognize that the relationship between measures of BuChE activity and TCP/Cr excretion is dynamic and that averaging the values for each measure throughout the year could possibly obscure or blunt the relationship between the two measures.…”
Section: Discussionsupporting
confidence: 90%
“…The spring sample was given a weight of 1 month because chlorpyrifos is typically used on home gardens and farms during a 1-month period in the spring when crops emerge. The samples taken during the baseline and 1 year physical examinations were each given a weight of 5.75 months (Burns et al, 2006).…”
Section: Exposure Assessmentmentioning
confidence: 99%
“…Chlorpyrifos is the major representative of the organophosphorus insecticides that are widely used in agriculture and even with all restrictions of their use, they still account for 50% of all pesticide applications worldwide. These compounds receive an increasing consideration as potential endocrine disrupters [21][22][23][24]. Chlorpyrifos is rapidly metabolized and excreted in the urine.…”
Section: Methodsmentioning
confidence: 99%
“…The study population was previously described in publications by Burns et al (2006) and Albers et al (2004aAlbers et al ( , b, c, 2007. Briefly, the study group consisted of 53 CPF manufacturing workers and a referent group of 60 workers in the Saran manufacturing process with no occupational exposure to organophosphate pesticides or ChE inhibitors (Table 1).…”
Section: Study Populationmentioning
confidence: 99%